Optimization of Inulin Hydrolysis by Penicillium lanosocoeruleum Inulinases and Efficient Conversion Into Polyhydroxyalkanoates - Corrado, Iolanda; Cascelli, Nicoletta; Ntasi, Georgia; Birolo, Leila; Sannia, Giovanni; Pezzella, Cinzia (Frontiers in Bioengineering and Biotechnology, 2021)
Inulin, a polydisperse fructan found as a storage polysaccharide in the roots of several plants, represents a renewable non-food biomass resource for the synthesis of bio-based products. Utilization of inulin containing feedstocks requires the integration of processes, including inulinase production, saccharification of inulin and microbial fermentation for the conversion of released sugars into added-value products. In this work, a new microbial source of inulinase production, P. lanosocoeruleum, was identified through the screening of a fungal library. Inulinase production using inulin as C-source was optimized, reaching up to 28 U mL-1 at the 4th day of growth. The fungal inulinase mixture (PlaI) was characterized in terms of pH and Temperature stability and activity profile, and its isoenzymatic composition investigated by proteomic strategies. Statistical experimental design was used to optimize inulin hydrolysis, analysing the effect of different variables, such as pH, Temperature and enzyme amount. In the best conditions (T, 44.5 °C; pH, 5.3; substrate concentration, 60 g L-1; enzyme loading, 40 U gsubstrate -1), up to 90% inulin conversion into fructose was achieved within 24 h. The integration of PlaI in a process for Polyhydroxyalkanoates (PHA) production by Cupriavidus necator from inulin was tested both in Separated Hydrolysis and Fermentation (SHF) and Simultaneous Saccharification and Fermentation (SSF). A maximum of 3.2 g L-1 of PHB accumulation, corresponding to 82% polymer content, was achieved in the SSF, laying the basis for profitable utilization of PlaI mixture in inulin-based biorefineries.